Solar and infrared radiation measurements - Vignola, Frank 1945- (Energy and the environment, 2012)
"Written for students and professionals, this reference explores the various types of solar radiation measurements and how they operate. The book gives the reader a step-by-step approach to the set-up, operation, and maintenance of a solar monitoring station. The book provides the background and terminology needed to understand the uses and requirements of various solar monitoring radiometers, and it gives an overview of the various solar radiation instruments. It also discusses the calibration and maintenance necessary for instruments in the lab and field, as well as covering the traceability of calibrations to international standards"--